The reliabilty and validity of a revised version of the How I Think Questionnaire for men who have intellectual disabilities - Daniel, Matthew R. (Psychology, crime & law, 2018)
The aim of this study was to revise an existing measure of distorted cognitions, creating the How I Think Questionnaire - Intellectual Disabilities (HIT-IDs), and to investigate the reliability and validity of the revised questionnaire. To achieve our aims, we recruited 97 men with intellectual disabilities (IDs), with or without a history of engaging in criminal behaviour, and interviewed them on two occasions, inviting them to complete the HIT-IDs, along with measures of moral development and empathy. The results indicated that the internal consistency of the HIT-IDs was acceptable, and the test-retest reliability was good. The HIT-IDs discriminated well between offenders and non-offenders, and as expected, correlated positively with a measure of moral development and negatively with a measure of empathy. The HIT-IDs is a reliable and valid measure for use with men who have IDs.